Assessment of Water Availability and Demand Balance at Air Keluar Spring, Hutumury Watershed, Ambon City - Nelda Maelissa; Julius Mulyono; Renny James Betaubun; Rudi Serang (Fakultas Teknik, Universitas Katolik Widya Mandala Surabaya, 2026)
The availability of clean water is a key indicator of sustainable infrastructure, particularly in island and urban regions where water sources are vulnerable to climate and land-use change. This study assesses the balance between water availability and demand at the Air Keluar Spring located within the Hutumury watershed, Ambon city. The research aims to evaluate whether the existing discharge can meet the current and projected water demand in Sirimau district and to identify the technical and environmental factors influencing the imbalance between supply and demand. The methodology integrates field discharge measurement, overlay analysis of land-use change (2018-2022), and clean water demand estimation following SNI 6728.1.2015 standards, supported by secondary data from PDAM Ambon, BMKG, and BPS. The results indicate that the natural discharge fluctuates between 0 and 4783 m3/s, with an annual average of 2.3 m3/s, yet only 0.04m3/s is effectively utilised for public supply. Meanwhile, the current water demand in Sirimau district is 0.379 m3/s and is projected to rise to 0.394m3/s by 2030. This operational deficit of approximately 0.339 m3/s (29,300 m3/day) is primarily due to reduced infiltration capacity following a 44% decrease in forest cover in the upstream watershed. The study concludes that water scarcity in Ambon city is not caused by limited natural resources but by inefficient utilisation and declining environmental function. Technical recommendations include expanding intake and reservoir capacity, reducing non-revenue water, and restoring upstream vegetation to enhance baseflow stability and ensure long-term water sustainability.